Stress-induced symptom exacerbation: Stress increases voiding frequency, somatic sensitivity, and urinary bladder inflammation when combined with low concentration cyclophosphamide treatment in mice - Girard, Beatrice M.; Campbell, Susan E.; Vizzard, Margaret A. (Frontiers in Urology, 2023)
Symptom exacerbation due to stress is prevalent in many disease states, including functional disorders of the urinary bladder (e.g., overactive bladder (OAB), interstitial cystitis/bladder pain syndrome (IC/BPS)); however, the mechanisms underlying the effects of stress on micturition reflex function are unclear. In this study we designed and evaluated a stress-induced symptom exacerbation (SISE) mouse model that demonstrates increased urinary frequency and somatic (pelvic and hindpaw) sensitivity. Cyclophosphamide (CYP) (35 mg/kg; i.p., every 48 hours for a total of 4 doses) or 7 days of repeated variate stress (RVS) did not alter urinary bladder function or somatic sensitivity; however, both CYP alone and RVS alone significantly (p ≤ 0.01) decreased weight gain and increased serum corticosterone. CYP treatment when combined with RVS for 7 days (CYP+RVS) significantly (p ≤ 0.01) increased serum corticosterone, urinary frequency and somatic sensitivity and decreased weight gain. CYP+RVS exposure in mice significantly (p ≤ 0.01) increased (2.6-fold) voiding frequency as we determined using conscious, open-outlet cystometry. CYP+RVS significantly (p ≤ 0.05) increased baseline, threshold, and peak micturition pressures. We also evaluated the expression of NGF, BDNF, CXC chemokines and IL-6 in urinary bladder in CYP alone, RVS alone and CYP+RVS mouse cohorts. Although all treatments or exposures increased urinary bladder NGF, BDNF, CXC and IL-6 content, CYP+RVS produced the largest increase in all inflammatory mediators examined. These results demonstrated that CYP alone or RVS alone creates a change in the inflammatory environment of the urinary bladder but does not result in a change in bladder function or somatic sensitivity until CYP is combined with RVS (CYP+RVS). The SISE model of CYP+RVS will be useful to develop testable hypotheses addressing underlying mechanisms where psychological stress exacerbates symptoms in functional bladder disorders leading to identification of targets and potential treatments.